2018
DOI: 10.18433/jpps29811
|View full text |Cite
|
Sign up to set email alerts
|

Icariside II Attenuates Chronic Hydrocephalus in an Experimental Subarachnoid Hemorrhage Rat Model

Abstract: Purpose To investigate the role of ICA II in subarachnoid hemorrhage (SAH)-  related chronic hydrocephalus. Methods A two hemorrhage injection model of SAH was created in Sprague Dawley rats (6-8 weeks). A total of 125 rats were randomly assigned into five groups: Sham group, SAH group, SAH+ ICA II (1 mg/kg) group, SAH + ICA II (5 mg/kg) group, and SAH + ICA II (10 mg/kg) group. TGF-β1, phospho-Smad2/3, connective tissue growth factor (CTGF), and procollagen type I carboxy-terminal propeptide (PICP) were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…As a major downstream mediator of TGF-β1/Smad signaling in many cell types, CTGF is regarded as an important amplifier of the pro-fibrogenic action of TGF-β1 in a variety of tissues [ 56 , 57 ]. CTGF expression is also significantly increased following aSAH [ 58 , 59 ]. In experimental aSAH models, TGF-β1 concentrations in CSF and protein TGF-β1 levels are significantly increased in periventricular brain tissues [ 60 , 61 ].…”
Section: Tgf and Its Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a major downstream mediator of TGF-β1/Smad signaling in many cell types, CTGF is regarded as an important amplifier of the pro-fibrogenic action of TGF-β1 in a variety of tissues [ 56 , 57 ]. CTGF expression is also significantly increased following aSAH [ 58 , 59 ]. In experimental aSAH models, TGF-β1 concentrations in CSF and protein TGF-β1 levels are significantly increased in periventricular brain tissues [ 60 , 61 ].…”
Section: Tgf and Its Antagonistsmentioning
confidence: 99%
“…Some TGF-β1 antagonists and TGF-β1 signaling pathway inhibitors alleviate chronic hydrocephalus and improve behavioral outcomes in rat aSAH models [ 58 , 59 ]. Decorin, a member of the small leucine-rich extracellular matrix proteoglycans, has exhibited significant inhibitory effects on the TGF-β1/Smad/CTGF axis, protecting against extracellular matrix accumulation with antifibrotic effects [ 59 , 63 ].…”
Section: Tgf and Its Antagonistsmentioning
confidence: 99%
“…CSF amyloid protein, nerve cell adhesion molecule-L1 (L1CAM), nerve cell adhesion molecule-1 (NCAM-1), and other proteins involved in nerve development are highly correlated with PHH in premature infants ( 24 ). Clinically, it is observed that there are high levels of proteins in the cerebrospinal fluid of patients with hydrocephalus, such as thrombopoietin, carbonicanhydrase-I (CA-I) and peroxidase-2 (Prx-2) ( 25 ), TGF-β1 ( 26 ), S-100protein, glial fibrillary acidic protein (GFAP) ( 27 , 28 ), neuron-specific enolase (NSE), and vascular endothelial growth factor ( 29 ). Absorption decreases after the accumulation of a large number of proteins in the ventricular system ( 30 ), leading to increased osmotic pressure and promotion of hydrocephalus ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, literature reports on hydrocephalus center on the risk factors or prediction models of a disease, whereas the pathogeneses of these diseases have common characteristics, which are gradually being recognized by the public. PHH is considered an important factor in the poor prognosis of ICH 4 , IVH 5 , SAH 6 , and TBI 7 . However, predictive models for PHH are lacking.…”
Section: Introductionmentioning
confidence: 99%